BINA IMAN KAUM MUDA SEBAGAI UPAYA MENINGKATKAN KEHIDUPAN MENGGEREJA OMK DI STASI TUMBANG KAMAN - Mira Santika; Silvester Adinuhgra; Paulina Maria E. W (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
This study aims to find out the participation and the activities of Youth in church life in Tumbang Kaman station. The method used in this research process is a qualitative descriptive method with data collection techniques through interviews, observation and documentation. With this approach, the author wants to know the experience of informants regarding youth participation in church life. Data analysis technique in this study uses qualitative data analysis of the Miles and Huberman models which are divided into 3 stages, namely data reduction, data display, conclusion / verification. Informants are people who provide data or information to the author in a study. The informants expected by the author to provide information consisted of parish priests, young people, catechists and other adult Catholics. In this study there were 12 informants who provided data and information to the author.